2018
DOI: 10.17796/1053-4628-42.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Evaluation of Ozone on Dentinal Lesions in Young Permanent Molars using the Stepwise Excavation

Abstract: Ozone gas had a significant antimicrobial effect in deep class I carious lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 27 publications
1
15
0
1
Order By: Relevance
“…(-), <10 3 CFUÁmL À1 ; (þ), À10 3 CFUÁmL À1 ; (þþ), 10 4 CFUÁmL À1 ; (þþþ), 10 4 -10 5 CFUÁmL À1 ; (þþþþ), >10 5 CFU/mL. Our data agree with Safwat et al [11], who found that gaseous ozone had a strong antimicrobial effect on cariogenic bacteria both in vitro and ex vivo and can be used as an adjuvant in caries therapy, unlike other studies [13] that have shown that 20% of S. mutans, 6.7% of Fusobacterium nucleatum, 13.4% of Bifidobacterium spp. and 6.7% Eubacterium spp.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…(-), <10 3 CFUÁmL À1 ; (þ), À10 3 CFUÁmL À1 ; (þþ), 10 4 CFUÁmL À1 ; (þþþ), 10 4 -10 5 CFUÁmL À1 ; (þþþþ), >10 5 CFU/mL. Our data agree with Safwat et al [11], who found that gaseous ozone had a strong antimicrobial effect on cariogenic bacteria both in vitro and ex vivo and can be used as an adjuvant in caries therapy, unlike other studies [13] that have shown that 20% of S. mutans, 6.7% of Fusobacterium nucleatum, 13.4% of Bifidobacterium spp. and 6.7% Eubacterium spp.…”
Section: Resultssupporting
confidence: 91%
“…A further study argues that 60 s ozone application results in the removal of most cariogenic microorganisms [10]. While the antibacterial properties of ozone and its role in creating suitable conditions for restoration of dental tissue mineral structures provide a strong argument for its use in the management of dental caries, some studies contradict these favourable results [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Dentistry is constantly searching for treatments that cause less discomfort to patients. This is also important for dentists working in the context of the pandemic, which requires professional preventive and minimally invasive approaches to the management of caries ( 7 ).New technologies such as cavity preparation by oscillation (ultrasound) ( 8 ), lasers ( 9 ), ozone ( 10 ), and chemomechanical caries removal agents ( 11 ) have been used. Most of these methods involve a high cost and may lead to tooth hypersensitivity, contributing to painful sensations, especially in children.Chemomechanical caries removal is a non-invasive technique that aims to dissolve necrotic tissues, facilitating the removal of the tissue softened manually with blunt-tip instruments.…”
Section: Introductionmentioning
confidence: 99%
“…Baseado nisso, observa-se uma incoerência a respeito dos protocolos para implementação da ozonioterapia, que pode ser explicada devido a uma falta de estudos na área e a dificuldade de se trabalhar com o gás em ambiente clínico, por conta de sua instabilidade. Porém, como estratégia de gerenciamento alternativo, o ozônio continua sendo recomendado devido à sua poderosa capacidade de inativar microrganismos, somado ao fator de haver evidências crescentes de que ele pode ser empregado como um agente terapêutico útil no tratamento odontológico, seja em relação à periodontite associada a bactérias, vírus e fungos (Kshitish & Laxman, 2010), estomatite protética (Muller et al, 2007), irrigação de canais radiculares (Cardoso et al, 2008), limpeza da cavidade após remoção da biomassa cariogênica (Safwat et al, 2018) ou desinfecção de matérias de uso clinico (Savabi et al, 2018).…”
Section: Discussionunclassified